2011
DOI: 10.1007/s12237-011-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies Mortality Patterns of Commercial Bivalves in Relation to Estuarine Salinity Fluctuation

Abstract: Fluctuations in salinity may cause huge economic losses in estuaries with exploited commercial bivalves owing to their effect on mortality of these species. However, the same decrease in salinity does not affect all species in the same way, so it is interesting to study the effect of salinity from a multispecies standpoint. In the management of exploited bivalve beds, it is important to know the tolerance thresholds of the species, not only in cases of extremely low salinities but also over prolonged periods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…The shellfish bed located in Lombos do Ulla, in the Ría de Arousa, used to be among those with the highest cockle catch in Galicia. High cockle mortality in this bed occurred occasionally due to very low salinity associated with heavy rains because of its location in the mouth of the Ulla River, the main tributary of the Ría de Arousa (Parada et al 2012). Two pathological conditions have been associated with periodic episodes of cockle mortality in this bed: one is disseminated neoplasia and the other is characterised by large foci of heavy haemocytic infiltration of connective tissue of various organs (Carballal et al 2001, Villalba et al 2001.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The shellfish bed located in Lombos do Ulla, in the Ría de Arousa, used to be among those with the highest cockle catch in Galicia. High cockle mortality in this bed occurred occasionally due to very low salinity associated with heavy rains because of its location in the mouth of the Ulla River, the main tributary of the Ría de Arousa (Parada et al 2012). Two pathological conditions have been associated with periodic episodes of cockle mortality in this bed: one is disseminated neoplasia and the other is characterised by large foci of heavy haemocytic infiltration of connective tissue of various organs (Carballal et al 2001, Villalba et al 2001.…”
Section: Introductionmentioning
confidence: 94%
“…Ruditapes philippinarum (75 t), R. decussatus (40 t) and Venerupis corrugata (8 t), all of which are sympatric with cockles (CIMA unpublished). The estuarine character of the area involves wide salinity fluctuation; occasionally, sharp salinity decreases caused by heavy rain leads to high shellfish mortality (Parada et al 2012). …”
Section: Shellfish Bed Of Lombos Do Ullamentioning
confidence: 99%
See 1 more Smart Citation
“…Not much work, however exists on the salinity decrease in the estuary due to execution of hydroelectric projects in the upstream areas causing almost constant release of freshwater into the estuary following power generation. In a rather isolated study related to the second scenario Parada et al (2012), reported the mortality of estuarine molluscan community on account of salinity decline in the estuary of Ulla River of Spain due to an upstream hydroelectric project. Salinity and substratum composition (for instance, sand-silt-clay mix) are the main factors influencing the estuarine molluscs (Harkantra 1975a, Kanaya andKikuchi, 2008;Mohan and Velayudhan 1998, Parker 1959, Sundaram and Shafee 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity and substratum composition (for instance, sand-silt-clay mix) are the main factors influencing the estuarine molluscs (Harkantra 1975a, Kanaya andKikuchi, 2008;Mohan and Velayudhan 1998, Parker 1959, Sundaram and Shafee 1989. In the case of Ulla estuary, salinity reduction directly *Address correspondence to this author at the Energy and Wetlands Research Group, Centre for Ecological Sciences, Indian Institute of Science, Bangalore -560012, India;Tel: 91-80-22933099/22933503;Ext: 107;Fax: 91-80-23601428/23600085/23600683;E-mail: cestvr@ces.iisc.ernet.in or in synergy with other factors, caused the bivalve mortality when its level declined below the optimum or lasted for long periods (Parada et al 2012). …”
Section: Introductionmentioning
confidence: 99%